The Politics of NDC Pension Scheme Diffusion : Constraints and Drivers - Guardiancich, Igor; Weaver, R. Kent; Demarco, Gustavo; Dorfman, Mark C. (World Bank, Washington, DC, 2019)
Nonfinancial defined contribution (NDC) schemes offer governments desirable properties in terms of efficiency, fairness, and financial sustainability and an opportunity to deflect the blame for pension cuts. Yet adoptions of NDC schemes largely ground to a halt and several countries retreated from NDC implementation after legislation. Lack of support from powerful international actors is partly to blame, as is the perceived rigidity of NDC in reducing room for policy maneuver. Correct implementation requires substantial administrative capacity. Less demanding automatic stabilizing mechanisms undercut the appeal of NDC in the European Union. Thus, while being an important option for policy makers and a benchmark against which to measure alternative reforms, NDC is unlikely to become the dominant pension design choice anytime soon.